Three Dimensions Analysis of The Main Character in UP Movie - Ni Putu Intan Gustianingsih; I Gusti Ayu Gede Sosiowati; I Komang Sumaryana Putra (Udayana Journal of Social Sciences and Humanities, 2023)
The aim of this study is to analyse the three dimensions of the main character in UP movie. The data which are used in this study are taken from a movie entitled UP. This study applied a theory proposed by Egri (1960) to analyse the three dimensions of the character. The data were collected by using documentation method and note taking technique. Descriptive and qualitative method were used to analyse the data. Based on the analysis, it shows that the main character in UP movie is Carl Fredricksen. In the movie, it shows all of the three dimensions of the character. The physiological dimension of Carl is Carl is an elderly. Based on the sociological dimension, Carl is a widower, a retired man, and he has a bad relationship with construction workers. Based on psychological dimension, Carl was quiet and shy when he was child, after the death of his wife he becomes short-tempered and stubborn but actually a nice person, Carl is faithful and loves his wife, and he also a smart person.